Nurse entrepreneurship in UK – critical review - Haine, Sally (2010)
Abstract The aim of the study was to explore nurse educators’ opinions, beliefs, perceptions and attitudes towards the subject of entrepreneurship in nursing. The objectives were: to discover whether nurse educators’ share their opinions with their students and so potentially influence them; to ascertain whether entrepreneurship would be or is currently encouraged amongst nursing students by nurse educators’; and to examine whether the views of nurse educators could potentially impact the beliefs, perceptions and attitudes of nursing students and therefore future nurses. This study expands on the little that is known about nurse entrepreneurship and what nurse educators do and do not know and illuminates and provides reason for knowledge deficits and discordant attitudes and opinions found. Current literature and health policies emphasise the need for an increased focus on nursing entrepreneurship due to the concept becoming increasingly relevant to contemporary healthcare. Despite this, very little is known about the knowledge and perceptions held by nurse educators towards entrepreneurship. There is no qualitative research exploring nurse educators’ perceptions towards nurse entrepreneurship in the UK. Participants for the research were selected from a large school of nursing in the East Midlands involved in the education of nurses with a background in nursing. The study adopted a qualitative approach using semi-structured interviews. The data was analysed manually using a thematic approach, using theory and literature to interpret what the seven participants said. The findings corroborate that nurse entrepreneurship is not a familiar term to nurse educators. However, the majority of nurse educators had heard about it and were able to identify key characteristics, skills and activities of nurse entrepreneurs. Limitations to this research have been acknowledged. This study highlights the need for further research surrounding this subject, to ensure nurse educators as well as student nurses and qualified nurses have a good understanding of the opportunity for nurse entrepreneurship.